(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless sensor network is extensively worn to check the spot (or) region. Diminutive amount of nodes are deployed to sense, transmit the information. To augment the life span of nodes, different types of routing algorithm are used. Grid structure aids to get better lifetime of the network by partition the spot into number of grids. The proposed method helps to beat the issues to loss the energy at the time of transmitting the data from Sensor Nodes (SN) to Cluster Head (CH) and to the Base Station (BS). Virtual grid recital facilitates to boost the energy by energy consumption. It supports to broadcast the data quickly. BS carries out the entire task resembling cluster head selection, cluster formation, Grid formation and isolated node recognition etc. Each cell is divided into equal number of cells in grid and it allows to communicating the node for data transmission easily using shortest path algorithm. EVGA proves it increases the lifetime of the node and it consumes energy.